Pronival ramparts: origin and development of terminology - Hedding, David W. (ERDKUNDE, 2016)
Pronival ramparts are debris ridges formed at the downslope margins of perennial or semi-permanent snowbeds at the foot of bedrock cliffs. The close spatial proximity and morphological similarities of pronival ramparts to modified talus sheets and cones as well as protalus rock glaciers, moraines and landslides has led to difficulties in correctly identifying ramparts. Nevertheless, these landforms have been documented across the globe and, as a result, terms have been developed in different languages. However, the use and meaning of rampart terminology, particularly across several languages, are not consistent. This paper chronicles the origin of the term ‘pronival rampart’ and assesses its use in English language literature and exposes readers to terms from other languages and how their use may differ. Lastly, this paper highlights that, since the meaning of terms denoting pronival ramparts varies between languages, readers should be cognisant of the meaning of the term in a respective language as this may have implications for how pronival ramparts are identified in the context of talus-derived landforms. The paper also discusses whether ramparts are part of a non-developmental or developmental morphological continuum of talus-derived landforms.